Construction sector: End of the boom at new buildings - Martin Gornig; Claus Michelsen (DIW Weekly Report, 2018)
New residential construction, in particular apartment complexes, has driven the growth in Germany's construction industry in recent years. In 2018 and 2019 the volume of new construction will continue to expand. However, its rate of expansion will decrease and the boom of recent years will come to an end. After years of strong growth, having even occasionally surpassed the ten-percent mark, the German Institute for Economic Research expects to see a definite slowdown in the growth rates for new residential construction. Taking into account the sharply rising construction prices the real growth rates drop on to approximately one percent. The additional momentum in new non-residential construction is not likely to compensate for the end of the boom in new residential construction. Therefore the focus will shift to renovation and modernization of the existing building stock. By 2019 at the latest, these should have a higher growth rate than that of new housing. In nominal terms, the German Institute for Economic Research anticipates growth in renovation activity of around 7.5 percent for the existing housing stock and 3.5 percent growth in the non-residential sector. The greater momentum of activity around the building stock, including energy efficiency upgrades, will also help meet Germany's climate targets. In view of the nation's tight urban housing market, policy makers would do well to counteract the foreseeable end of the boom in new housing construction by establishing incentives for urban development and redensification as well as supporting the construction of additional residential space in urban development zones.
Keywords: E32; E66; 330; construction industry; residential construction; public infrastructure; economic outlook